The Role of Non-specific and Specific Immune Systems in Poultry against Newcastle Disease - Hewajuli, Dyah Ayu; Dharmayanti, NLPI (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2015)
Newcastle disease (ND) is caused by avian paramyxovirus-1 which belong to Avulavirus genus and Paramyxoviridae family. The birds have abnormalities in humoral (bursa fabricius) and cellular (thymus and spleen) lymphoid organs. Lesions decrease the immune system. Immune system consists of non-specific and specific immune systems. The main components of non-specific immunity are physical and chemical barrier (feather and skin or mucosa), phagocytic cells (macrophages and natural killer), protein complement and the mediator of inflammation and cytokines. Interferons (IFNs) belong to a group of cytokines that play a major role in the nonspecific or innate (natural) immunity. The virulent ND virus encodes protein of V gene can be suppressed IFN type I. This leads to non-specific immune system fail to respond to the virulent strains resulting in severe pathogenicity. The defense mechanism of the host is replaced by specific immunity (adaptive immunity) when natural immunity fails to overcome the infection. The specific immune system consists of humoral mediated immunity (HMI) and cell-mediated immunity (CMI). The cells of immune system that react specifically with the antigen are B lymphocytes producing the antibodies, T lymphocytes that regulate the synthesis of antibodies and T cells as effector or the direct cytotoxic cells. Both non-specific and specific immunities are complementary against the invasion of ND virus in the birds. The objective of this article is to discuss the role of non specific and specific immune system in ND. Key words: Newcastle disease, limphoid organs, non-specific, specific immunity